A modeling study to define guidelines for antigen screening in schools and workplaces to mitigate COVID-19 outbreaks - Yong Dam Jeong; Keisuke Ejima; Kwang Su Kim; Shoya Iwanami; William S. Hart; Robin N. Thompson; Il Hyo Jung; Shingo Iwami; Marco Ajelli; Kazuyuki Aihara (Communications Medicine)
Abstract Background In-person interaction offers invaluable benefits to people. To guarantee safe in-person activities during a COVID-19 outbreak, effective identification of infectious individuals is essential. In this study, we aim to analyze the impact of screening with antigen tests in schools and workplaces on identifying COVID-19 infections. Methods We assess the effectiveness of various screening test strategies with antigen tests in schools and workplaces through quantitative simulations. The primary outcome of our analyses is the proportion of infected individuals identified. The transmission process at the population level is modeled using a deterministic compartmental model. Infected individuals are identified through screening tests or symptom development. The time-varying sensitivity of antigen tests and infectiousness is determined by a viral dynamics model. Screening test strategies are characterized by the screening schedule, sensitivity of antigen tests, screening duration, timing of screening initiation, and available tests per person. Results Here, we show that early and frequent screening is the key to maximizing the effectiveness of the screening program. For example, 44.5% (95% CI: 40.8–47.5) of infected individuals are identified by daily testing, whereas it is only 33.7% (95% CI: 30.5–37.3) when testing is performed at the end of the program duration. If high sensitivity antigen tests (Detection limit: $$6.3× {10}^{4}$$ 6.3 × 10 4 copies/mL) are deployed, it reaches 69.3% (95% CI: 66.5–72.5). Conclusions High sensitivity antigen tests, high frequency screening tests, and immediate initiation of screening tests are important to safely restart educational and economic activities in-person. Our computational framework is useful for assessing screening programs by incorporating situation-specific factors.